The Symbolism in Sylvia Plath’s Poems - Yanti, Novi; Pandey, Nishi (IJLHE: International Journal of Language, Humanities, and Education, 2019)
This study aims to analyze the symbols that Sylvia Plath used in her poems. Therefore, the objectives of the study can be stated as follow: to explore the symbolism in Sylvia Plath’s poems. The approach of this paper is to highlight the symbols which are frequently used by Sylvia Plath in her poems. The data analysis technique used is non-interactive with an emphasis on content analysis. According to the discussion, there are six symbols found such as colors (red, white, black, and pink). Women are also found as one of the symbols. Next, the use of natural objects such as water and the moon. Most of his poetry also uses religious symbols. Lastly, Sylvia Plath uses death as a symbol in her poetry.